Analysis of Stylistic Features in Ben Weilow’s Song ‘Vodun Life Spirit’ - Ayodele Adebayo ALLAGBÉ; Franck AMOUSSOU (Revue Hybrides)
This paper aims to examine the linguistic or stylistic features in Ben Weilow’s song entitled ‘Vodun Life Spirit’. Drawing on stylistics, especially on Leech and Short’s checklist of linguistic and stylistic categories (lexical categories, grammatical categories, figures of speech, and cohesion and context) (Leech and Short, 2007), and on the descriptive qualitative research method, the study specifically analyzes how the singer organizes language to encode meaning(s) in his aforementioned song. The findings reveal that Ben Weilow employs such lexical features as ‘Vodun Life Spirit’, ‘Vodun Love Spirit’, ‘Mother Vodun Maou’ and ‘Mother Vodun Maou Lissa’. He also uses terms like‘’Dambada Houèdo’, ‘Tchango’, ‘Hêviosso Fire’, etc. As it appears, these lexical features are abstract nouns which refer to spiritual agents, the main spiritual agent being ‘Mother Vodun Maou Lissa’ as it performs all the agentive actions in the text. Moreover, the results show that Ben Weilow uses, in varying proportions, sentence length and structure. They unveil too that the singer employs figures of speech like metaphor, allusion, metonymy, personification, etc. in his song. Finally, the findings indicate that Ben Weilow deploys lexical cohesion, reference and conjunction, the most dominant type being lexical cohesion. In conclusion, it can be established that all the linguistic features identified in the song are deployed to represent ‘Vodun’ as a positive spiritual force which pervades human life and everything. Therefore, this suggests that Vodun protects and empowers its children or worshippers against evil, provides them with all their (im)material needs and also gives them eternal joy.